Does Dowry Size Correlate with Marital Harmony? A Socio-Legal Analysis of Muslim Communities in Cibeureum District, Tasikmalaya, Indonesia - Yanti Haryanti (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2026)
Purpose – Mahr (dower) constitutes an essential obligation in Islamic marriage and is intended to symbolize commitment rather than impose an economic burden. However, in many contemporary Muslim communities, the increasing value of mahr has become associated with social prestige, potentially creating financial pressure and affecting family relationships. This study examines the relationship between mahr determination and family harmony in Cibeureum District, Tasikmalaya, from the perspective of the sociology of Islamic law. Design/methodology/approach – The study employs a descriptive qualitative approach. Data were collected through field observations and in-depth interviews with community members in Cibeureum District. The findings were analyzed using a sociological approach to Islamic law to explore how religious norms interact with local social values in shaping mahr practices and perceptions of marital harmony. Findings – The study reveals that the practice of demanding high-value mahr has evolved into a social convention driven primarily by modernization, social prestige, and symbolic status rather than customary or religious obligations. While some participants perceive a high mahr as a marker of family honor and marital stability, others argue that family harmony is more closely associated with mutual agreement, affordability, and the absence of coercion in determining the mahr. These findings indicate that the value of mahr itself is not the primary determinant of harmonious family relationships; instead, fairness, mutual consent, and economic capacity play more significant roles. Research implications/limitations – The study is limited to one district and reflects a specific socio-cultural context. Future research may undertake comparative studies across different regions or employ quantitative methods to examine broader patterns of mahr practices and marital outcomes. Originality/value – This study contributes to the sociology of Islamic family law by demonstrating that mahr functions as a socially negotiated institution whose meaning extends beyond legal obligation. It highlights the importance of contextualizing mahr within contemporary social realities and offers practical recommendations for premarital education and policy development through collaboration with local Offices of Religious Affairs (KUA).